1996
DOI: 10.1021/ma960882f
|View full text |Cite
|
Sign up to set email alerts
|

First Success in Direct Analysis of Microscopic Deformation Mechanism of Polydiacetylene Single Crystal by the X-ray Imaging-Plate System

Abstract: The deformation mechanism of a polymer crystal has been directly clarified for the first time using an imaging-plate X-ray structural analysis system for a polydiacetylene single crystal subjected to a tensile stress at room temperature as well as at 122 K. That is to say, the small displacements of the constituent atoms of the planar-zigzag skeletal chain could be successfully detected. The change in the internal coordinates such as bond length and bond angle, which were induced by tensile stress, has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…These spectral changes cannot be interpreted as a result that the polymerization further proceeds ordinarily. It is well known that PDs exhibit chromatic transition from the blue phase, which is usually obtained directly from the monomer, to the red phase by several stimulations including UV irradiation [1][2][3][4][5][6][7][8][9][10]. Though the product directly obtained from HTDY on Au(1 1 1) has a quite small conjugation length and cannot be the blue phase PDs, a transition to a red-phase-like state may occur by UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These spectral changes cannot be interpreted as a result that the polymerization further proceeds ordinarily. It is well known that PDs exhibit chromatic transition from the blue phase, which is usually obtained directly from the monomer, to the red phase by several stimulations including UV irradiation [1][2][3][4][5][6][7][8][9][10]. Though the product directly obtained from HTDY on Au(1 1 1) has a quite small conjugation length and cannot be the blue phase PDs, a transition to a red-phase-like state may occur by UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The photopolymerization of diacetylene derivatives has been studied in single crystals [1][2][3][4], self-assembled monolayers (SAMs) [5] and Langmuir-Blodgett (LB) films [6][7][8][9][10][11]. Upon polymerization, the regularity in molecular packing is not lost and the conjugated diacetylene moiety C"CAC"C of the monomer is converted into a repeat unit of the acetylenic type CAC"CAC by connecting the outer carbons in the adjacent molecules with new double bonds .…”
Section: Introductionmentioning
confidence: 99%
“…The torsion angle between substituent groups plays an important role in the appearance of conjugated polydiacetylene, as nearly flat structures are proposed to appear blue whereas strongly twisted structures appear red. 19 This structural/colorimetric transformation of PDA can be generated by various external stimuli, such as temperature 20,21 , mechanical stress 22,23 , pH 24 , ionic strength 25 , or bio-interactions 26,27 . It is demonstrated that by incorporating biological receptors in the PDA liposome bilayer, the binding of analytes to receptors may change the conformation of the polymer backbone providing a colorimetric response for a variety of biological targets 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…1 When exposed to external stimuli, including heat, pH, stress, ions, solvent, and biological substances, PDA can undergo conformational changes that cause a pronounced color change from blue to red and a dramatic shift in the λ max absorption of the polymer. [2][3][4][5][6][7][8] The intriguing stimuli-induced color change makes PDA of interest in a variety of applications, such as colorimetric chemosensing or biomolecular sensing. PDA-based biosensors have been proven to be sensitive to a wide range of analytes, such as proteins, lipophilic enzymes, bacteria, viruses, and pharmacologically active compounds.…”
Section: Introductionmentioning
confidence: 99%